Genome wide conditional mouse knockout resources. (2016) - Kaloff, C.; Anastassiadis, K.; Ayadi, A.; Baldock, R.; Beig, J.; Birling, M.-C.; Bradley, A.; Brown, S.D.M.; Bürger, A.; Bushell, W.; Chiani, F.; Collins, F.S.; et al.
Abstract : The International Knockout Mouse Consortium (IKMC) developed high throughput gene trapping and gene targeting pipelines that produced mostly conditional mutations of more than 18, 500 genes in C57BL/6N mouse embryonic stem (ES) cells which have been archived and are freely available to the research community as a frozen resource. From this unprecedented resource more than 6000 mutant mouse strains have been generated by the IKMC in collaboration with the International Mouse Phenotyping Consortium (IMPC). In addition, a cre-driver resource was established including 250 C57BL/6 cre-inducible mouse strains. Complementing the cre-driver resource, a collection comprising 27 rAAVs expressing cre in a tissue-specific manner has also been produced. All resources are easily accessible from the IKMC/IMPC web portal (www.mousephenotype.org ). The IKMC/IMPC resource is a standardized reference library of mouse models with defined genetic backgrounds enabling the analysis of gene-disease associations in mice of different genetic makeup and should therefore have a major impact on biomedical research.